Inference on Reliability for Cascade Model - Gogoi, Jonali; Borah, Munindra (Journal of Informatics and Mathematical Sciences, 2012)
In this paper we consider two cases to obtain the system reliability for cascade model. For the first case we consider one-parameter exponential strength and two-parameter gamma stress. Under this assumption the reliability of the system in general terms is obtained. Secondly we consider two-parameter exponential strength and one-parameter gamma stress to obtain an expression for the reliability of a 3-cascade system. For both the cases all stress-strengths are random variables with given density. In all these cases numerical integration is used to evaluate the reliability for cascade system. Some numerical values of R( 1 ), R( 2 ), R( 3 ) and R_3 for particular values of the parameters involved are tabulated at the end.